Food safety lessons for cannabis-infused edibles - Knutson, Kathy (Academic Press, an imprint of Elsevier, 2020)
Food Safety Lessons for Cannabis-Infused Edibles details the world of cannabis-infused edibles and the way its manufacturing is evolving as the industry moves from isolation to regulatory compliance. The cannabis industry has unique challenges as cannabis-infused edibles are not regulated as food, drugs or dietary supplements at the federal level. Despite these current conditions, the industry is aware of the need to examine the safety of these edibles and prepare for a future of federal compliance. The book looks at the cannabis industry through a scientific lens to increase awareness and expertise in food safety within the field of cannabis-infused edibles. --